The Constitution of 1949 and the historical-constitutional background of the social and democratic state under the rule of law. - Jurado Fernández, Julio (2026)
This essay analyzes the historical and constitutional background of the 1949 constitution based on the liberal model established in the 1871 constitution and its evolution towards the formation of the social and democratic state under the rule of law.